Gender Budgeting in Europe Developments and Challenges (Springer International Publishing, 2018)
This book takes a broad look at conceptual and practical applications of gender budgeting in Europe. It comprises three linked sections that: work through conceptual definitions of gender budget analysis, exploring how it can be framed and constructed as a gender equality policy; investigate case studies across Europe; and examine challenges for implementation. This statement publication explores conceptual and methodological variations evidence in practice in Europe and the challenges of adoption and implementation in different political and institutional contexts. It brings together historical and current conceptual developments and tensions; approaches, methodologies, and tools in practice across Europe; activism, actors and agency and the engagement of formal institutions at all levels of government with feminist policy changes and feminist analysis and activists. This text is fascinating reading for students, scholars, policy makers and activists.